Agroecology: the key role of arbuscular mycorrhizas in ecosystem services - Gianinazzi, Silvio; Gollotte, Armelle; Binet, Marie-Noëlle; van Tuinen, Diederik; Redecker, Dirk; Wipf, Daniel (Mycorrhiza, 2010)
The beneficial effects of arbuscular mycorrhizal (AM) fungi on plant performance and soil health are essential for the sustainable management of agricultural ecosystems. Nevertheless, since the ‘first green revolution', less attention has been given to beneficial soil microorganisms in general and to AM fungi in particular. Human society benefits from a multitude of resources and processes from natural and managed ecosystems, to which AM make a crucial contribution. These resources and processes, which are called ecosystem services, include products like food and processes like nutrient transfer. Many people have been under the illusion that these ecosystem services are free, invulnerable and infinitely available; taken for granted as public benefits, they lack a formal market and are traditionally absent from society's balance sheet. In 1997, a team of researchers from the USA, Argentina and the Netherlands put an average price tag of US $33 trillion a year on these fundamental ecosystem services. The present review highlights the key role that the AM symbiosis can play as an ecosystem service provider to guarantee plant productivity and quality in emerging systems of sustainable agriculture. The appropriate management of ecosystem services rendered by AM will impact on natural resource conservation and utilisation with an obvious net gain for human society.